Minoan civilization. - Alexiou, Stylianos; Ridley, Cressida (Heraklion : Spyros Alexiou, 1969)
Describes the palace of Minos, the Minoans and Mycenaeans, and the rise and fall of Crete plus recent discoveries on that island.
Includes bibliographical references.
Keywords: Minoans; Civilization, Mycenaean; Minoans; Civilization, Mycenaean; Crete (Greece) -- Antiquities; Crete (Greece) -- Antiquities